Studies on the development of food attractants catching noctuid mouths (Lepidoptera: Noctuidae) - Nagy, Antal; Szarukán, István; Gém, Ferenc; Nyitrai, Rita; Tóth, Miklós (Acta Agraria Debreceniensis, 2014)
The monitoring of the most dangerous noctuid pests (Lepidoptera: Noctuidae) can be performed by species specific pheromone traps. Recently the development of traps catching female moths became the main objective of the studies. We studied the synergistic effect of vine and beer as natural additive on the effectiveness of baits containing isoamyl alcohol and acetic acid in Forró and Debrecen-Ondód. The addition of vine and beer had positive effect on catches and it was significant in case of two dangerous pest species Agrotis segetum and Lacanobia oleracea. The synergistic effect was also significant with regard to the number of detected species especially in case of lower abundances and rare species.